Elevated extinction risk of low-elevation populations of two songbirds on the Taiwan island - Xuntao Ma; Yadan Liu; Zhang Zhang; Mingwang Zhang; Feng Dong (Avian Research)
Prevailing concerns on mountainous biodiversity are concentrated on the impacts of climate change at higher elevations. However, the lower elevations are facing additional human disturbance and are expected to suffer from higher extinction risk but have attracted less conservation attention. Here, we employed population genomics to compare extinction risk two common songbirds—the Vinous-throated Parrotbill (Sinosuthora webbiana) and the Rufous-capped Babbler (Cyanoderma ruficeps)—at lower and higher elevations on the Taiwan island. As the result, we observed decreased genetic diversity and increased genetic load and thus elevated extinction risk in the low-elevation populations of both birds in the eastern slope of the Central Mountains on the Taiwan island. In contrast, genetic-load patterns of both birds in the western slope might be confused by substantial gene flow across lower and higher elevations. These results, on the one hand, call for conservation efforts to lower elevations in mountains and, on the other hand, highlight the importance of population connection in maintaining population viability under impending global change.